2021
DOI: 10.1002/lary.29797
|View full text |Cite
|
Sign up to set email alerts
|

Above and Beyond: Periorbital Suspension for Endoscopic Access to Difficult Frontal Sinus Pathology

Abstract: Objectives/Hypothesis: The periorbital suspension (PS) is an advanced adjunctive technique performed during endoscopic approaches to frontal sinus pathology that would be too far lateral or superior to address using traditional endoscopic transnasal approaches. The objectives of this study are to characterize the utility of this technique for frontal sinus pathology, determine anatomic limitations, and assess clinical outcomes following surgical treatment.Study Design: Prospective case series. Methods: Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Bilateral anterior table, NOE, and concurrent posterior table fractures were also fixed successfully. Because periorbital suspension approaches can reach almost any area of the frontal sinus, 5 the only contraindications would be sizeable lacerations that do not require enlargement (fracture can be repaired directly) or if craniotomy is required and the anterior table will already be exposed for fixation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bilateral anterior table, NOE, and concurrent posterior table fractures were also fixed successfully. Because periorbital suspension approaches can reach almost any area of the frontal sinus, 5 the only contraindications would be sizeable lacerations that do not require enlargement (fracture can be repaired directly) or if craniotomy is required and the anterior table will already be exposed for fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior table fractures were repaired using our previously described techniques. 1,2,5 Briefly, a Draf IIB or Draf III was used to approach the fractures. Using a 70-degree endoscope, we inserted a curved suction or frontal sinus curette to reduce the inferior or medial sections of the fracture, followed by reduction of the superior or lateral fragments (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies, including a randomized controlled trial, have demonstrated that mucosal-free grafts and vascularized pedicled flaps confer long-term patency of frontal sinus neo-ostium in larger dimensions following the Draf 3/endoscopic-modified Lothrop procedures at significantly better rates than leaving the remaining bone bare. [23][24][25][26][27][28][29][30][31][32][33][34][35] Placement of steroid-eluting implants can be considered for preservation of patent outflow in the immediate postoperative period as well as for consistent topical medical therapy to the surgical bed. Steroid-eluting stents have consistently shown superiority in maintaining frontal sinus patency in CRSwNP.…”
Section: Frontal Sinusmentioning
confidence: 99%